Epidemiological correlates of depression in females at an infertility clinic of government medical hospital- a cross sectional study - Ukey, Ujwala Uttamrao; Wadhva Sharma, Sarita (International Journal Of Community Medicine And Public Health, 2023)
Background: Infertility affects lives of millions of people worldwide which includes the couples themselves as well as extends further to their families, wider communities also. Moreover, in contrast to the usual belief, the problem is faced by men and women both. Infertility-related stress adversely affects all dimensions of health, quality of life of the couples and relationship with family. Methods: This cross sectional study was carried out in the outpatient department (OPD) of obstetrics and gynecology during a period of two months (August and September 2022). The study subjects comprised of women in the age group of 18-45 years. Data was collected using interview techniques by a pre designed questionnaire. Statistical analysis was carried out nu epi info software. Results: A total sample of 113 was covered in the present study. The mean age of the study subjects was 28.38 years, range being 21 to 37 year. Depression of varying levels was detected in 76 (67.25%) of the study participants. However, 32 (32.75%) females were normal without any detection of depression. Mild depression was observed in 15 (13.27%), moderate in 62 (49.56%) and remaining 5 (4.42%) had severe depression. Conclusions: Depression of a varying level of severity is common occurrence in the women attending infertility clinic. Though role of socio demographic factors is not statistically proven in relation to depression in the study, their role cannot be denied.